2022
DOI: 10.1038/s41377-022-00850-4
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared III–V semiconductor lasers epitaxially grown on Si substrates

Abstract: There is currently much activity toward the integration of mid-infrared semiconductor lasers on Si substrates for developing a variety of smart, compact, sensors based on Si-photonics integrated circuits. We review this rapidly-evolving research field, focusing on the epitaxial integration of antimonide lasers, the only technology covering the whole mid-to-far-infrared spectral range. We explain how a dedicated molecular-beam epitaxy strategy allows for achieving high-performance GaSb-based diode lasers, InAs/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 121 publications
3
19
0
Order By: Relevance
“…[25,94] Furthermore, the mismatch of crystal polarity between III-V and Si (IV) leads to antiphase boundaries which are 2D defects generating a local excess or lack of electrical charges and hence affect the efficiency of the laser devices. [95] In order to overcome the above-mentioned challenges, Wang et al [35] demonstrated an optically pumped DFB laser array using selective area growth of III-V gain material in confined regions. The schematic of the laser array is illustrated in Figure 6(a).…”
Section: Iii-v Integration On Si Through Direct Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…[25,94] Furthermore, the mismatch of crystal polarity between III-V and Si (IV) leads to antiphase boundaries which are 2D defects generating a local excess or lack of electrical charges and hence affect the efficiency of the laser devices. [95] In order to overcome the above-mentioned challenges, Wang et al [35] demonstrated an optically pumped DFB laser array using selective area growth of III-V gain material in confined regions. The schematic of the laser array is illustrated in Figure 6(a).…”
Section: Iii-v Integration On Si Through Direct Growthmentioning
confidence: 99%
“…[ 25,94 ] Furthermore, the mismatch of crystal polarity between III–V and Si (IV) leads to antiphase boundaries which are 2D defects generating a local excess or lack of electrical charges and hence affect the efficiency of the laser devices. [ 95 ]…”
Section: Iii–v Lasers On Siliconmentioning
confidence: 99%
“…Optoelectronic semiconductors that exhibit excellent electronic and optical properties have significant application potential in solar cells, 1,2 light-emitting diodes (LEDs), 3,4 laser diodes, 5 bioimaging, 6 and photodetectors. 7,8 Throughout, the crystal structures of optoelectronic semiconductors are mainly comprised of octahedral and tetrahedral structures.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 For example, high performance 2.3 μm wavelength mid-infrared laser diodes epitaxially grown on (001) Si have been demonstrated by a few groups. 7,8 Also, InAs/InAsSb type-II superlattice nBn photodetectors monolithically integrated on Si with a high specific detectivity of 1.5 × 10 10 Jones at 200 K have also been reported. 9 Despite significant strides in the improvement of device performance, challenges still remain in the growth of highquality metamorphic GaSb buffer layers on Si, which ultimately determines the device quality.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The short-wavelength infrared (SWIR) band is an important electromagnetic spectral region for gas sensing, molecular spectroscopy, military missile tracking, and thermal imaging. , Among the various materials available for SWIR optoelectronics, Sb-based III–V semiconductors have been the main choice because of their direct band gap, strong absorption coefficients, and high electron mobility. , Different kinds of detectors and emitters were developed by using such materials, but they have to be grown on relatively expensive and small-sized wafers such as GaSb or InSb. Therefore, monolithic integration of Sb-based optoelectronic devices on a Si wafer has recently drawn strong attention, not only for reducing the epitaxial cost but also for light-source integrated Si photonics applications. , For example, high performance 2.3 μm wavelength mid-infrared laser diodes epitaxially grown on (001) Si have been demonstrated by a few groups. , Also, InAs/InAsSb type-II superlattice nBn photodetectors monolithically integrated on Si with a high specific detectivity of 1.5 × 10 10 Jones at 200 K have also been reported …”
Section: Introductionmentioning
confidence: 99%